EVALUASI KURIKULUM PENDIDIKAN PAI - Darwin Robany; Adi Saputra (JIP: Jurnal Ilmu Pendidikan, 2025)
The evaluation of the Islamic Religious Education (PAI) curriculum is a crucial process to ensure that the objectives of Islamic education are optimally achieved through the implementation of an effective, adaptive, and relevant curriculum that aligns with learners’ needs. This article examines various curriculum evaluation approaches used to analyze the alignment between learning objectives, instructional content, teaching methods, and learning outcomes within the context of PAI education. Employing a literature review method, this study explores evaluation models such as CIPP, Stake, and Tyler, which have been widely referenced in curriculum development. The findings indicate that PAI curriculum evaluation should ideally be conducted comprehensively, not only focusing on cognitive aspects but also incorporating assessments of learners’ spiritual, social, and emotional development. Furthermore, the study reveals that the primary challenges in implementing the PAI curriculum include limited integration of Islamic values with contemporary developmental needs and insufficient utilization of technology in the learning process. These findings carry significant implications for policymakers, curriculum developers, and educational practitioners, encouraging the strengthening of evaluation strategies, refinement of curriculum design, and enhancement of teacher competencies to foster more meaningful, contextual, and effective PAI learning.